Situation Report: Hungary, 3 July 1974 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Hungarian National Bank Borrows 100,000, 000 dollars from US and Canadian Banks Greater Dynamism in Hungarian-Yugoslav Economic Relations Closed Production Technology Expanding Hungary's Wheat Production Reaches World Level; Wheat Exports Increase Summer Session of the National Assembly